High-dose versus weekly cisplatin definitive chemoradiotherapy for HPV-related oropharyngeal squamous cell carcinoma of the head and neck. (April 2017) - Perez, Cesar Augusto; Wu, Xiaoyong; Amsbaugh, Mark J.; Gosain, Rahul; Claudino, Wederson M.; Yusuf, Mehran; Roberts, Teresa; Jain, Dharamvir; Jenson, Alfred; Khanal, Sujita; Silverman, Craig I.; Tennant, Paul; et al.
Highlights: HPV status is the strongest predictor of overall survival (OS) in SCCHN. Definitive CRT with HDC and WC similar toxicity profile in patients with HPV-related SCCOPx. CRT with HDC had better EFS when compared with WC possibly because increased distant failure rates. Abstract: Objectives: To compare the outcomes and toxicity of high-dose cisplatin (HDC) versus weekly cisplatin (WC) definitive chemoradiotherapy (CRT) for patients with human papillomavirus (HPV) related oropharyngeal squamous cell carcinoma (SCCOPx). Methods: All patients with p16 positive SCCOPx treated with definitive CRT with cisplatin between 2010 and 2014 at a single institution were retrospectively reviewed. CTCAE v 4.03 toxicity criteria were used. The Kaplan-Meier method was used to estimate event-free survival (EFS) and the overall survival (OS). Results: Of the 55 patients included, 22 were patients treated with HDC at dose of 100 mg/m 2 on days 1 and 22; and the remaining 33 patients were treated with WC at 40 mg/m 2 . Both cohorts received a median total dose of cisplatin of 200 mg/m 2 . At median follow-up of 31 months, there was one local failure and no distant failures in the HDC cohort. In the WC group, there were 6 total failures (2 local, 4 distant). Estimated 2-year EFS was better in HDC cohort as compared to WC (96% vs. 75%; p = 0.04). There was no significant difference in 2-year OS (95% vs. 94%; p = 0.40). Weight loss, gastric tube dependence at six months, acute renal injury and grade 3 or 4 hematological toxicity were all similar between both groups. Conclusions: HPV-related SCCOPx treated with definitive CRT with either HDC or WC had similar toxicity profile. HDC had better EFS when compared with WC and this seems to be driven by increased distant failure rates, although the OS was similar.